The Adaptive Optics National Workshop (ADONI) of the National Institute for Astrophysics (INAF) - , (Il Colle di Galileo, 2016)
A national workshop dedicated to all INAF researchers and associates interested in the application of adaptive technologies to astronomy and other fields.